The prevalence and associated charateristics of patients with Kaposi at Pietersburg Hospital, Limpopo Province - Mukhithi, Tshimangadzo (My University, 2023)
Background Among the most prevalent malignancies associated with AIDS, Kaposi Sarcoma (KS) is one of them. In the developing countries, it is a significant cause of morbidity and mortality, resulting in 2500 deaths per year and it accounts for approximately more than 10% of all cancer deaths in Sub Saharan Africa. Due to the availability of ART, the prevalence of KS has decreased in western nations, but it has increased in Sub-Saharan Africa due to higher rates of co-infection with HIV and the Kaposi Herpes virus (KSHV). Hence, the present study investigated the prevalence of KS in Limpopo Province in the era of ART roll out in South Africa. Aim and objectives. To assess the prevalence and associated characteristics of patients with Kaposi Sarcoma at Pietersburg Hospital, Limpopo Province in South Africa. Methods The study was a retrospective cross sectional descriptive study in adult individuals (years ± 40yrs) conducted at Pietersburg Medical Oncology clinic over 3 years period (1st January 2015 to 31st December 2018). There was no sample size calculation, and convenient study sample sampling was used. Due to the present study small size, the study’s patients were not divided into their respective years. Results A total of 117 patients were included in the data analysis. There was no statistical difference in gender groups (p-value = 0.51). The study reported that the overall prevalence of Kaposi Sarcoma at Pietersburg Hospital was 4%. The predominant subtypes were 94% with AIDS associated KS and 6% endemic. Majority of patients (93%) were HIV positive and only 7% were HIV Negative. Males (72%) had increased percentage of KS as compared to their females (45%) counter parts. All the patients were of African descent with no case of Classic KS seen over the study period. Conclusion The study highlighted the positive impact of anti-retroviral therapy (ART) in reducing the prevalence of Kaposi Sarcoma and the late diagnosis of HIV KS with almost 50% of patients not on ART at the time of diagnosis. The study has reported that although KS is still being diagnosed in patients with HIV at Pietersburg Hospital, there was lower prevalence of KS, which does not differ from that of other South African studies. More studies are still warranted using larger sample sizes on patients in order to further investigate the relationship of HIV+ patients and KS.
Thesis (M.Med. (Internal Medicine)) -- University of Limpopo, 2023
Keywords: Kaposi Sarcoma; HIV; Prevalence; Ard; Kaposi's sarcoma; AIDS (Disease); HIV (Viruses); Antiretroviral agents